The investigation of hepatoprotective and antioxidant properties of Osmanthus fragrans on experimental model of chronic alcoholic liver damage in vivo - Hubich, Aksana I.; Shpak, Anton P. (Experimental Biology and Biotechnology, 2025)
The possibility of Osmanthus fragrans decoctions to stabilise the values of biochemical markers of liver damage and lipid peroxidation in rats on an experimental model of chronic alcohol intoxication was analysed. It was found that Osmanthus fragrans decoction has the antioxidant and hepatoprotective effects on rats with experimental alcoholic liver damage, exceeding the effect of the comparison drug – the pharmacy hepatoprotective herbal collection «Phytolekar dlya pecheni» («Phytolekar for liver»). The introduction of the analysed decoction into the diet of animals with alcoholic liver damage for 20 days contributed to a decrease in TBA-active products content in their liver homogenate by 75.5 % and an increase in SH-groups level by 129.3 % compared to similar indicators of rats suffering from this experimental pathology but not receiving the drug and was accompanied by a tendency to an increase of catalase activity. A decrease in peroxidation processes intensity in the liver, in turn, ensured normalisation of the biochemical markers of liver damage such as concentration of total bilirubin and albumin, activity of alanine aminotransferase and alkaline phosphatase in the experimental animals serum. These effects may be due to the high content of bioflavonoids, phenolic acids, vitamins of group E, unsaturated fatty acids and ionones in the composition of Osmanthus fragrans, which exhibit antioxidant properties.